A novel mechanism of autophagy-associated cell death of vasopressin neurons in familial neurohypophysial diabetes insipidus - Hagiwara, Daisuke; Grinevich, Valéry; Arima, Hiroshi (Cell & tissue research, 2019)
Familial neurohypophysial diabetes insipidus (FNDI), characterized by delayed-onset progressive polyuria and loss of arginine vasopressin (AVP) neuron, is an autosomal dominant disorder caused by AVP gene mutations. We previously generated a knock-in mouse model for FNDI, which recapitulated the phenotype of human FNDI. To address the mechanisms underlying AVP neuron loss, we subjected FNDI mice to intermittent water deprivation, which accelerated the phenotype and induced AVP neuron loss within a relative short period. Electron microscopic analyses revealed that aggregates were confined to a sub-compartment of the endoplasmic reticulum (ER), ER-associated compartment (ERAC), in AVP neurons of FNDI mice under normal conditions. In contrast, aggregates scattered throughout the dilated ER lumen, and phagophores, autophagosome precursors, emerged and surrounded the ER containing scattered aggregates in FNDI mice subjected to water deprivation for 4 weeks, suggesting that failure of ERAC formation leads to autophagy induction for degradation of aggregates. Furthermore, the cytoplasm was entirely occupied with large vacuoles in AVP neurons of FNDI mice subjected to water deprivation for 12 weeks, at which stage 30-40% of AVP neurons were lost. Our data demonstrated that although autophagy should primarily be a protective mechanism, continuous autophagy leads to gradual loss of organelles including ER, resulting in autophagy-associated cell death of AVP neurons in FNDI mice.